Analisis Kualitatif Kebutuhan Transportasi Desa Kasus: Desa Pulosari, Sukabumi, Jawa Barat - Alvita Seda; Dwinarosa Allamanda; Jimmy Chandra; Melina Melina (Universitas Prasetiya Mulya, 2019)
The research is held to find out the need of villagers toward the ideal transportation in rural area. The data was collected using several methods, including observation, interview, and FGD with the villagers in Desa Pulosari, Sukabumi, Jawa Barat. The collected data was analyzed using Coding Scheme: Customer Needs (Goffin et al., 2012) method. Based on the coding scheme, there are two main needs for villagers toward rural transportation, i.e the need for vehicles to improve villagers’ welfare and economic conditions and the need for suitable and safe vehicles for mobilization in rural areas.